From Catacombs to Freedom: Ukrainian Greek Catholic Church in Face of Socio-political Changes in Central and Eastern Europe (late 1980s – early 1990s) - Taras Bublyk (Politeja, 2023)
The paper analyzes the details of the movement for legalizing the Ukrainian Greek Catholic Church (UGCC) in the late 1980s and early 1990s, which acquired a special momentum in face of socio-political changes in the USSR and the other countries of Central and Eastern Europe. The UGCC, which was officially liquidated by the Soviet government in 1946, managed to form underground structures and continue pastoral activities. In the 1980s, the human rights organization Committee for the Protection of the Ukrainian Catholic Church (UCC) was formed and began to actively seek the official legalization of the UGCC. Western politicians and the Ukrainian diaspora became important factors influencing Soviet power. A combination of various factors, both internal and external, at the end of 1989 resulted in the authorities being forced to recognize the right of Greek Catholics to legally register their communities. Thus, a long ‘catacomb’ period came to an end and the UGCC received an opportunity to develop.